ISOLASI DAN IDENTIFIKASI RIZOBAKTERI DARI TANAMAN KOPI ROBUSTA (Coffea canephora) YANG TERSERANG Prattylenchus coffeae - Siti Rosida; Iis Nur Asyiah; Imam Mudakir (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2017)
Abstract: The majority of Indonesian coffee production is robusta coffee. The increasing coffee production with large scale causes changes in the soil ecosystem, it profitable for development of pest populations and diseases in coffee. One of pests that attack coffee plant is Pratylenchus coffeae. Rizosphere is ground around the roots measuring about 1 mm and surrounds entire surface of roots. Rizobacteria are beneficial bacteria that live in a saprophyte in a rhizosphere. This research aims to perform the isolation and identification of rhizobacteria from robusta coffee plants in Kali Bendo plantation, Banyuwangi Regency, East Java. In this research, the determination of research location is using purposive sampling technique, while the sampling technique is using random sampling method. The results showed there were 8 isolates obtained Bacillus sp. with isolate code 3R, G20, and I13, Micrococcus sp. with isolate code L20, Acinetobacter sp. with isolate code 4R and C13 and Pseudomonas sp. with isolate code M20 and A13. Key words: identification, rizobacteria, rizosphere